Structural Study of the Germanium-Aluminum-Borate Glasses by Solid State NMR and Raman Spectroscopies - Franco, Douglas F. [UNESP]; Fernandes, Roger Gomes [UNESP]; Santagneli, Silvia Helena [UNESP]; De Oliveira, Marcos; Eckert, Hellmut; Nalin, Marcelo [UNESP] (American Chemical Society (ACS), 2020)
Glasses in the system (85-x)GeO2-(x)B2O3-10Na2O-4Al2O3-1PbO, which are used as matrices for rare-earth ion containing magneto-optic glasses have been prepared and their thermal and structural properties have been characterized by differential scanning calorimetry, Raman scattering, and solid state NMR spectroscopies. Besides showing the features of the corresponding borogermanate binary glasses, the Raman spectra also reveal new features consistent with the occurrence of B-O-Ge connectivities. One- and two-dimensional 23Na, 27Al, and 11B NMR spectra reveal monotonic structural changes as a function of composition, reflecting the competition of the three network former species for charge compensation by the network modifier cations. Aluminum is found in a predominantly four-coordinated environment. Its anionic functionalization and, with second priority, that of the boron oxide component take precedence over that of the germanium oxide component. The glass transition temperature decreases with increasing B2O3 content and shows an excellent correlation with the average network connectivity deduced from the NMR data.